Comparative study on histological structure of Channa micropeltes Cuvier(1831)gill from the Lubuk Siam Lake and Sibam River, Riau Province - Hermawanto, Hermawanto; Efizon, Deni; Eddiwan, Eddiwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractSnakehead fish (Channa micropeltes) is one type of freshwater fish that lives in the Lubuk Siam Lake that has good water quality and the Sibam River that is polluted. The water condition may affectsthe fish health status in general, especially in the gills. A study aims to determine the differences of gills structure of C.micropeltes fish from the Lubuk Siam Lake and Sibam River has been conducted from August to September 2018. The gills samples were prepared for histological observation using paraffin method and stained with Hematoxylin-Eosin (HE), while the level of gills damage is studied using a Histopathological Alteration Index (HAI). Histological structure of thr gill of fish from both areas are different. The cell structure of the Sibam River fish has more abnormality compared with the cell structure of fish from the Lubuk Siam Lake. Result shown that the types of abnormality present were hyperplasia, odema and epitelium rupture. The HAI of the C. micropeltesfrom the Lubuk Siam Lake was 1, indicated that the gill was normal, while those the HAI of the C.micropeltes from the Sibam River was 8.33, indicated that the gill was normal.Keyword : Channamicropeltes, Lubuk Siam lake, Sibam River, Gill abnormality, HAI